Connecting the Dots in Education for Newly Arrived Migrant Students in Flanders - Laura Thomas; Britt Adams; Laura Emery; Thibaut Duthois; Ruben Vanderlinde; Melissa Tuytens (MDPI AG, 2022)
All over Europe, the rapidly increasing number of newly arrived migrant students (NAMS) not only transformed countries into ethnically diverse societies but also led to various challenges for the educational system in general and its schools and teachers in particular. In Flanders, education for NAMS has several limitations, such as an overrepresentation of NAMS in vocational tracks and a lack of interaction between reception and mainstream education teachers. The central thesis of this paper is that building up networks between the actors involved in the education for NAMS in Flanders may offer a solution for much of the formulated critiques. The paper starts off with an overview of the Flemish educational system and pays particular attention to reception education, its central actors, and the issues they are experiencing. Next, an argumentation for social networks as a potential solution for the critiques is built up, followed by a potential future agenda for education for NAMS in Flanders, riddled with network-related opportunities. The central aim of the paper is to generate fresh insight into education for NAMS, by linking its shortcomings to the strength of building up networks and collaboration, or put differently, connecting the dots.